1980
DOI: 10.1111/j.1432-1033.1980.tb04796.x
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence Studies of the Calcium Binding to Whiting (Gadus merlangus) Parvalbumin

Abstract: The calcium binding by parvalbumin of whiting (Gadus merlangus) has been studied using tryptophanyl fluorescence characteristics. Titration of Ca2+-free parvalbumin with Ca2+ leads to a very pronounced blue shift, narrowing and intensification of the fluorescence spectrum. These spectral changes proceed in two stages reflecting the existence of at least three forms which can be interpreted as (a) the protein without Ca2+, (b) with one Ca2+ and (c) with two bound Ca2+ ions/molecule. The fluorescence of these fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
45
1

Year Published

1995
1995
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(54 citation statements)
references
References 20 publications
(18 reference statements)
7
45
1
Order By: Relevance
“…[21] It has been shown that such an approach is extremely sensitive to the accumulation of any intermediate state. [21,22] Figure 3 clearly shows that the phase diagram plotted for the GdmCl-induced unfolding of BCA II consists of three linear parts, corresponding to 0 ± 0.1, 0.1 ± 1.0 and 1.0 ± 6.0 M GdmCl concentration. This reflects the existence of three independent transitions: N 6 I GdmCl any other structural parameter takes place.…”
Section: Resultsmentioning
confidence: 99%
“…[21] It has been shown that such an approach is extremely sensitive to the accumulation of any intermediate state. [21,22] Figure 3 clearly shows that the phase diagram plotted for the GdmCl-induced unfolding of BCA II consists of three linear parts, corresponding to 0 ± 0.1, 0.1 ± 1.0 and 1.0 ± 6.0 M GdmCl concentration. This reflects the existence of three independent transitions: N 6 I GdmCl any other structural parameter takes place.…”
Section: Resultsmentioning
confidence: 99%
“…The 'phase diagram' method, initially described by Burstein for the analysis of fluorescence data, is extremely sensitive for the detection of any intermediate states [21,22]. The essence of this method is to build up the diagram of I ( 1 ) versus I ( 2 ), where I ( 1 ) and I ( 2 ) are the fluorescence intensity values measured on wavelengths 1 and 2 under different experimental conditions when a protein is undergoing structural transformations.…”
Section: 'Phase Diagram' Methodsmentioning
confidence: 99%
“…Fluorescence data were analyzed according to the phase diagram method, which is sensitive for detecting any intermediate state [29], [30]. The essential point of this method is to build up a diagram of I λ1 versus I λ2 , where the I λ1 and I λ2 are the fluorescence intensities at two different emission wavelengths.…”
Section: Methodsmentioning
confidence: 99%